2015
DOI: 10.1136/bmjopen-2014-006984
|View full text |Cite
|
Sign up to set email alerts
|

Current pain education within undergraduate medical studies across Europe: Advancing the Provision of Pain Education and Learning (APPEAL) study

Abstract: ObjectivesUnrelieved pain is a substantial public health concern necessitating improvements in medical education. The Advancing the Provision of Pain Education and Learning (APPEAL) study aimed to determine current levels and methods of undergraduate pain medicine education in Europe.Design and methodsUsing a cross-sectional design, publicly available curriculum information was sought from all medical schools in 15 representative European countries in 2012–2013. Descriptive analyses were performed on: the prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 27 publications
(44 reference statements)
5
120
0
3
Order By: Relevance
“…Education, when provided, occurred within other subjects and tended to not use practical teaching methods. 16 In a survey of doctors in 49 LMICs, 90% considered their undergraduate training in pain management to be inadequate, and 80% did not receive formal training. The survey also found that postgraduate training was very variable.…”
Section: Staff Knowledge and Attitudesmentioning
confidence: 99%
“…Education, when provided, occurred within other subjects and tended to not use practical teaching methods. 16 In a survey of doctors in 49 LMICs, 90% considered their undergraduate training in pain management to be inadequate, and 80% did not receive formal training. The survey also found that postgraduate training was very variable.…”
Section: Staff Knowledge and Attitudesmentioning
confidence: 99%
“…21 In terms of pain management, a recent European survey concluded that pain teaching in many European medical schools fell short of what might be expected given the prominence and public health burden of pain. 22 In addition, there is continuing evidence that pain is still not optimally managed in hospital. 23 Enhancing undergraduate education in this clinical field can only be beneficial.…”
mentioning
confidence: 99%
“…Za sada nema jasno usvojenog stava ni o broju sati nastave, kao ni o intenzitetu kojim nastava treba da bude sprovedena. Opšte prihvaćeni stav je da postoji fragmentarna distribucija raspoloživih kadrova dostupnih za izvođenje nastave, da nastavni program nije struktuisan i da su na pomolu veliki izazovi koji nalažu ozbiljne promene i reorganizaciju u cilju poboljšanja edukacije o terapiji akutnog postoperativnog bola 5 .…”
Section: Edukacija Kadrovaunclassified